2009
DOI: 10.1007/s11240-009-9528-8
|View full text |Cite
|
Sign up to set email alerts
|

Agrobacterium-mediated genetic transformation of pineapple var. Queen using a novel encapsulation-based antibiotic selection technique

Abstract: A protocol for Agrobacterium-mediated transformation of a local 'elite' Indian variety (Queen) of pineapple [Ananus comosus (L.) Merr, family Bromeliaceae] has been established using a standard transformation vector (pCAMBIA 1304). High transformation efficiency, expressed as the mean percentage of transgenic microshoots regenerated from initial callus explants (20.6%) was achieved using a novel encapsulation-based, antibiotic selection procedure. The Agrobacterium-infected microshoots derived from callus expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
(11 reference statements)
0
8
0
Order By: Relevance
“…It is used to indicate transient and stable transformations (Serres et al 1992), and to estimate the relative contribution and strength of promoter elements in the transcriptional activation. Most recently, GUS histochemical assay was utilized in the production of markerfree Petunia hybrida and tomato (Khan et al , 2011, and in the production of a more efficient Agrobacterium tumefaciens-mediated transformation protocol in melon (Ntui et al 2010), in Lilium (Azadi et al 2010), in Petunia hybrida (Thirukkumaran et al 2009), in pineapple (Gangopadhyay et al 2009), in Piper colubrinum (Mani and Manjula 2011), in sesame (Yadav et al 2010), in…”
Section: Discussionmentioning
confidence: 99%
“…It is used to indicate transient and stable transformations (Serres et al 1992), and to estimate the relative contribution and strength of promoter elements in the transcriptional activation. Most recently, GUS histochemical assay was utilized in the production of markerfree Petunia hybrida and tomato (Khan et al , 2011, and in the production of a more efficient Agrobacterium tumefaciens-mediated transformation protocol in melon (Ntui et al 2010), in Lilium (Azadi et al 2010), in Petunia hybrida (Thirukkumaran et al 2009), in pineapple (Gangopadhyay et al 2009), in Piper colubrinum (Mani and Manjula 2011), in sesame (Yadav et al 2010), in…”
Section: Discussionmentioning
confidence: 99%
“…In the past, it has been found that, under appropriate in vitro conditions, the intrinsic and induced capability of plant cells and tissues to undergo different developmental stages of somatic embryogenesis is extremely critical (Zhang et al 2007). Several studies on in vitro regeneration by somatic embryogenesis in pineapple have been reported (Daquinta et al 1997;Firoozabady and Moy 2004;Rahman et al 2005;Firoozabady et al 2006;Gangopadhyay et al 2009). MS medium supplemented with decreasing concentration gradient of glutamine, KNO 3 and NH 4 NO 3 contributed to induce somatic embryogenesis in recalcitrant cotton cultivars (Ikram-ul-haq and Yusuf 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results are available as conference abstracts relating to the transformation of pineapple using both Agrobacterium and microprojectile-mediated gene transfer [3,4,8,9,11,14]. Recently, Gangopadhyay et al [10] reported Agrobacterium-mediated genetic transformation of pineapple cv. "Queen" using a novel encapsulation-based antibiotic selection technique.…”
Section: Estimation Of Iron and Zinc In Transformed Linesmentioning
confidence: 99%